Economies of Scope, Entry Deterrence and Welfare - PIRES, CESALTINA PACHECO (2014)
This paper develops a model where the incumbent may expand to a related market to signal economies of scope and deter entry in the former market. We show that the incumbent only expands when scope economies are large enough. Thus expansion is a signal of larger economies of scope and, for certain parameter values, leads to entry deterrence. Although our game is twoperiod, the expansion strategy creates a long-term advantage. We further investigate the implications of prohibiting an entry-deterrent expansion. A major finding is that, in our model, this prohibition always decreases consumer surplus. In terms of global welfare, the impact is ambiguous but negative for many parameter values.